BEST-PRACTICES PENDEKATAN SAINTIFIK PADA PEMBELAJARAN KIMIA DI SMA NEGERI 4 SAMPIT - Cita Indira (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2014)
This research is aimed to improve students’ activity through the implementation of scientific approach for chemistry courses at SMA N 4 Sampit. Observing, questioning, experimenting, analysing, and communicating as the component of scientific approach were used in chemistry class for students at science program grade XI and XII. To make meaningful learning, methods and medias that had been applying were chil book, concept map, memorization, experiment, field study, science aid, chart, cross word puzzle, science playing card, memory matric, peer learning, science tournament, poetry, and songs. This research shows scientific approach is able to improve student’s activity, proven by the improving score of learning success indicator at 40% to 85,9%. More specifically, the counting material such as stoichiometry and rate reaction can be applied to the method: chil book, and concept maps. Content that is a theory can be applied to the method: memorization, charta, cross word puzzle, science playing cards, memory matrix, science tournament, lifelong learning, poetry, and songs. The material can be applied to the experimental method: lab. work, field study, and science aid.